(Di‐tert‐butylphosphanylethyl)cyclopentadienylnickel Chelates with Alkyl, Alkenyl, Aryl, and Alkynyl Ligands: Hints to Cumulenylidene Resonance Forms. Issue 1 (3rd January 2018) - Kohser, Stefanie; Butenschön, Holger
Abstract : Cyclopentadienylalkylphosphane chelate complexes have been investigated in depth for many transition matals, but to a much lesser extent for nickel. On the basis of earlier investigations of cyclopentadienylalkylphosphane nickel chelates, a number of new alkyl, aryl, alkenyl, and alkynyl complexes, including some bearing functional groups, were prepared and fully characterized. These include for the first time di‐ and trimetallic complexes as well as compounds with a ferrocene unit as part of the extended π system. A number of quaternized 2‐pyridylethynyl complexes are presented, for which cyclovoltammograms, NMR spectroscopic data, and DFT calculations provide hints to a significant contribution of cumulenylidene resonance forms. Abstract : 2‐Pyridylethynylnickel chelate complexes are alkylated at the nitrogen atom, and cyclovoltammetry, NMR spectroscopy, and DFT calculations provide evidence for a significant contribution of cumulenylidene resonance forms in the quaternized complexes.